2011
DOI: 10.1002/cplu.201100022
|View full text |Cite
|
Sign up to set email alerts
|

Redox Chemistry of Third Phases Formed in the Cerium/Nitric Acid/Malonamide‐n‐Dodecane Solvent Extraction System

Abstract: Upon solvent extraction of the colorless solution 0.1 M Ce(NO3)3⋅6H2O in 3 M HNO3 with DMDBTDMA (N,N′‐dimethyl‐N,N′‐dibutyltetradecyl malonamide) at a concentration of 0.5 M in n‐dodecane (also a colorless solution), a yellow third phase is formed. In keeping with previous observations reported in the historical literature of solvent extraction, the yellow color was initially interpreted as an indication of the presence of tetravalent cerium, which is, coincidentally, yellow in aqueous HNO3. The valence quanda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 64 publications
0
25
0
Order By: Relevance
“…The radioactive ions can then be recovered from the ceriumcontaining solution by a process involving electrodialysis and ion-exchange [143], and the adsorption of Ce(IV) complexes has been investigated for this purpose [144], separating it from other lanthanides present in spent nuclear fuels. Ce(III) extraction has been contemplated in nuclear separation processes as PUREX (plutonium and uranium recovery by extraction) [145] and DIAMEX (diamide extraction) [146,147]. Cerium ions and oxides are well-known surrogates for plutonium and other actinide elements.…”
Section: Nuclear Decontamination and Decommissioningmentioning
confidence: 99%
“…The radioactive ions can then be recovered from the ceriumcontaining solution by a process involving electrodialysis and ion-exchange [143], and the adsorption of Ce(IV) complexes has been investigated for this purpose [144], separating it from other lanthanides present in spent nuclear fuels. Ce(III) extraction has been contemplated in nuclear separation processes as PUREX (plutonium and uranium recovery by extraction) [145] and DIAMEX (diamide extraction) [146,147]. Cerium ions and oxides are well-known surrogates for plutonium and other actinide elements.…”
Section: Nuclear Decontamination and Decommissioningmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16] This redox chemistry is relevant to both fundamental and applied research. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] For example, multi-configurational ground states have recently been revealed in several molecular and solid-state Ce(IV) materials. 25,[29][30][31][32][33][34][35][36][37] Moreover, X-ray absorption spectroscopy and density functional theory studies on tetravalent cerium have revealed considerable covalency and f orbital participation in Ce(IV)-L bonding.…”
Section: Introductionmentioning
confidence: 99%
“…Cerium(IV) oxide, or ceria, is an industrially important material with applications in glass polishing, organic catalysis, environmental remediation, solid‐oxide fuel cells, and as possible partial replacement for neodymium in NdFeB magnets [8,9] . Beyond its practical end‐usage, the ability to easily cycle between the +3 and +4 oxidation states leads to the use of Ce as a proxy element in studies of valence‐controlled solvent extraction separation of trivalent and tetravalent actinides and lanthanides in the PUREX (Plutonium Uranium Reduction EXtraction) process for nuclear fuel reprocessing [3,6–8,10] …”
Section: Introductionmentioning
confidence: 99%
“…Solvent extraction processes for Ce IV recovery using solvating extractants such as tributylphosphate (TBP) or diglycolamides in organic diluents are unstable at high acid or metal loading, manifested by the splitting of the organic phase into a dense metal/acid‐rich phase and a light diluent phase. Third‐phase formation is triggered by the polar solute‐induced aggregation of the amphiphilic ligand upon extraction into the organic phase and the eventual coalescence of reverse micellar aggregates into larger‐scale assemblies, resulting in a failure of the extraction process, and places an upper boundary on the applicable metal concentration in the feed solution [4,10–13] . In contrast to the undesired aggregation resulting in the organic phase separation, acidic aqueous biphasic systems (AcABS) rely on the inorganic acid content to drive the desired and reversible phase transition of a hydrophilic quaternary ammonium or phosphonium ionic liquids (ILs), thereby substituting the inorganic salt in traditional ABS [14] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation